2013
DOI: 10.1016/j.atmosenv.2013.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble projections of wildfire activity and carbonaceous aerosol concentrations over the western United States in the mid-21st century

Abstract: We estimate future wildfire activity over the western United States during the mid-21st century (2046–2065), based on results from 15 climate models following the A1B scenario. We develop fire prediction models by regressing meteorological variables from the current and previous years together with fire indexes onto observed regional area burned. The regressions explain 0.25–0.60 of the variance in observed annual area burned during 1980–2004, depending on the ecoregion. We also parameterize daily area burned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
309
3
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 237 publications
(323 citation statements)
references
References 37 publications
(52 reference statements)
10
309
3
1
Order By: Relevance
“…Other studies have shown linkages between a warmer climate and increased evaporative emissions from mobile sources (Rubin et al, 2006), increased electricity usage (Mideksa and Kallbekken, 2010), and increased wildfire activity over parts of the United States (Yue et al, 2013), all of which could lead to even greater health impacts from climate than shown here.…”
Section: Limitationsmentioning
confidence: 39%
“…Other studies have shown linkages between a warmer climate and increased evaporative emissions from mobile sources (Rubin et al, 2006), increased electricity usage (Mideksa and Kallbekken, 2010), and increased wildfire activity over parts of the United States (Yue et al, 2013), all of which could lead to even greater health impacts from climate than shown here.…”
Section: Limitationsmentioning
confidence: 39%
“…Although numerous studies have projected changes in burned area over the twenty-first century due to ACC, we are unaware of other studies that have attempted to quantify the contribution of ACC to recent forested burned area over the western United States. The near doubling of forested burned area we attribute to ACC exceeds changes in burned area projected by some modeling efforts to occur by the mid-twentyfirst century (29,30), but is proportionally consistent with midtwenty-first century increases in burned area projected by other modeling efforts (17,(31)(32)(33).…”
mentioning
confidence: 66%
“…Banerjee et al: Drivers of changes in stratospheric and tropospheric ozone al., 2014). The magnitudes of natural emission sources of tropospheric ozone precursors are also likely to be affected by future changes in climate and land use (Squire et al, 2014) through changes in, for example, wildfire activity (Yue et al, 2013), lightning activity (Grewe, 2009;Banerjee et al, 2014) and the amount of isoprene emitted from vegetation Pacifico et al, 2009).…”
mentioning
confidence: 99%